Disabled facilities in shopping malls: Malaysian perspective / Ahmad Ezanee Hashim ... [et. al] - Hashim, Ahmad Ezanee; Ismail, Faridah; Akida, Murni; Isnin, Zarina; Natasha, Khalil; Abdul Rahim, Mardhati (Faculty of Business and Management, 2011)
This paper identifies the level of satisfaction on present facilities provided in shopping malls in Klang Valley, Malaysia. Literature review, data collection on case study access audit, selected interviews and questionnaires combined with details from observations and photographs were used to explore on how to achieve friendly and accessible spaces for all. The audit examined predetermination designed criteria against existing building to measure the suitability and appropriateness of the building to people with sensory disabilities and mental disabilities. Findings revealed that weaknesses found are caused by poor design and planning, lack of enforcement on policies and limited guidelines. Recommendations for the future are highlighted with options and proposed guidelines in respect to the person with disabilities (PWDs) need. The finding has provided a benchmark for consultants, local authorities and those who have interest in local built environment.